(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The article discusses the problems of enhancing the cognitive activity of students at the stage of pre-university preparation and a number of tasks aimed at developing and improving the learning process when preparing students for entering a university.